PERAN GANDA ISTRI DALAM PEMENUHAN KEBUTUHAN RUMAH TANGGA PERSPEKTIF SOSIOLOGI HUKUM ISLAM - Nurhasmi Nurhasmi; Arisman Arisman (Al-Usroh : Jurnal Hukum Keluarga Islam, 2026)
This study aims to examine the dual role of wives in fulfilling household needs from the perspective of the sociology of Islamic law. The research uses a literature-based normative legal research method, this study connects Islamic family law, social change, and maqāṣid al-syarī'ah. The results of the study show that the economic participation of wives can be understood as an adaptive practice that is permissible if it is based on deliberation, does not transfer the main maintenance obligation from the husband, and maintains family harmony. Within the framework of maqāṣid, the role supports the protection of property (ḥifẓ al-māl), soul (ḥifẓ al-nafs), heredity (ḥifẓ al-nasl), and intellect (ḥifẓ al-'aql). This article offers an integrative reading between Islamic legal norms and contemporary family realities.